2016
DOI: 10.3389/fmars.2016.00154
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Composition of Polychaete Assemblages in the Aegean Coast of Turkey

Abstract: Benthic infaunal species and communities have been extensively used to evaluate quality of the marine environment. Within the MSFD, community composition is addressed most commonly through Descriptor 6 (Seafloor integrity), criterion 6.2 (Condition of benthic communities). At the same time, the Directive has stipulations for addressing and assessing indicators linked with pressures in an explicitly spatial manner. At larger scales, achieving this through point sampling may be impractical or unfeasible; hence p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 71 publications
0
9
0
7
Order By: Relevance
“…Astrophorids, such as the geodiids, Stelletta or Stryphnus, are massive sponges adapted to high-energy environments where they reach high densities (Knudby et al 2013, Beazley et al 2015) in contrast to hexactinellids or other demosponges that can have branching or tubular structures likely adapted to lower-energy regimes. The structureforming Geodia species in our study are found in areas with high primary production and fast currents that would provide high food supply needed to reach their large biomasses (up to 2 t found in a trawl set), as seen elsewhere in the Atlantic Ocean (Klitgaard & Tendal 2004, Fuller 2011, Murillo et al 2012, Knudby et al 2013.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Astrophorids, such as the geodiids, Stelletta or Stryphnus, are massive sponges adapted to high-energy environments where they reach high densities (Knudby et al 2013, Beazley et al 2015) in contrast to hexactinellids or other demosponges that can have branching or tubular structures likely adapted to lower-energy regimes. The structureforming Geodia species in our study are found in areas with high primary production and fast currents that would provide high food supply needed to reach their large biomasses (up to 2 t found in a trawl set), as seen elsewhere in the Atlantic Ocean (Klitgaard & Tendal 2004, Fuller 2011, Murillo et al 2012, Knudby et al 2013.…”
Section: Discussionmentioning
confidence: 65%
“…A full model including all covariate and quadratic terms was used to select the number of species archetypes. The covariates used were previously standardized to a mean of 0 and variance of 1 (Dunstan et al 2013, Galanidi et al 2016. The most parsimonious model was determined by comparing models with different species archetypes (G) using the Bayesian information criterion (BIC) (Schwarz 1978).…”
Section: Species Archetype Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, examining predictions of species' co‐occurrence patterns in concert with dispersal estimates using joint species distribution modeling could provide a way forward (Anderson, ; Kissling & Schleuning, ; Ovaskainen et al, ; Warton et al, ). Lastly, we do not explore how our model projections translate to assemblage‐level outcomes; however, novel multivariate techniques (e.g., archetype modeling) could enable exploration of this topic in future (Dunstan, Foster, & Darnell, ; Galanidi, Kaboglu, & Bizsel, ).…”
Section: Discussionmentioning
confidence: 99%